A real-world study of polyenyl phosphatidylcholine in the management of patients with metabolic dysfunction-associated fatty liver disease in China clinical practice - Pan, Yi; Xue, Feng; Wang, Shanshan; Zhong, Bihui; Zhan, Yutao; Wang, Qi; Xu, Youqing; Rao, Huiying; Mi, Yuqiang; Nan, Yuemin; Xu, Xiaoyuan; Popovic, Branko; et al. (Frontiers in Medicine, 2025)
Background/ObjectivesMetabolic dysfunction-associated fatty liver disease (MAFLD) is highly prevalent in China. Clinical evidence supporting the role of polyenyl phosphatidylcholine (PPC) in delaying liver fibrosis in patients with MAFLD is limited. Hence this study evaluated the effectiveness of PPC and its association with delaying progression of liver fibrosis in patients with MAFLD in China.MethodsThis multicenter, retrospective observational study included patients with type 2 diabetes mellitus or ≥2 metabolic dysregulations. Patients from the MAFLD cohort were divided into two groups to receive either PPC or control (no hepatoprotective treatment). The primary endpoint was the change in baseline fibrosis (FIB)-4 index at 12 and 24 weeks. The secondary endpoint involved comparison of changes in liver enzymes and blood lipid levels.ResultsAmong 22,705 patients with MAFLD who were treated with hepatoprotective drugs, 7,093 received PPC. Significant reduction in baseline fibrosis was observed at 24 weeks (PPC: −0.12 ± 0.62 vs. control: 0.11 ± 0.50, p = 0.034). Baseline aspartate aminotransferase (AST) levels significantly improved at 12 weeks (PPC: −6.25 ± 15.18 vs. control: −2.41 ± 15.40; p = 0.0392). In the PPC group, baseline alanine transaminase (ALT) levels decreased at 12- and 24-weeks compared to those of the control group, but results were not significant. PPC significantly reduced baseline total bilirubin at 12 weeks (p = 0.0122) and 24 weeks (p = 0.0010), and low-density lipoprotein cholesterol levels at 12 weeks (p = 0.0442).ConclusionPPC treatment can lower the risk of liver fibrosis and improve liver function and lipid profiles. Further validation is warranted in other ethnic groups in larger cohorts.